Pengaruh Model Pembelajaran Guided Discovery Berbantu Strategi Mnemonik terhadap Pemahaman Konsep Sistem Gerak - Juanengsih, Nengsih; Emalia, Eva; Siregar, Sillak Hasiany (Bioedukasi: Jurnal Pendidikan Biologi, 2019)
This study aims to determine the effect of Guided Discovery Learning (GDL) model with mnemonic strategy assistance on concept understanding of motion systems. The subject of this research were students of class XI at SMAN 1 Kota Tangerang Selatan academic year 2018/2019. The number of samples consisted of 40 students in the experimental group and 39 students in the control group. This research method used a quasi-experimental research design with the control group pre-test and post-test design. The sample of this research was taken by using a random sampling technique. This research used multiple-choice test instruments as many as 18 questions and 12 description questions and non-test instruments in the form of learning and teaching observation sheets and questionnaires. The data analysis of the two groups used the Mann-Whitney test. Based on data processing shows that the Asymp.Sig (2-tailed) value is 0.000 < 0.05, means H0 is refused. This research shows that there is an effect of guided discovery learning model with mnemonic strategy assistance on concept understanding of motion system.